Signatures of Thalamocortical Alpha Oscillations and Synchronization With Increased Anesthetic Depths Under Isoflurane - Jiang, Jingyao; Zhao, Yi; Liu, Jin; Yang, Yaoxin; Liang, Peng; Huang, Han; Wu, Yongkang; Kang, Yi; Zhu, Tao; Zhou, Cheng (Frontiers in Pharmacology, 2022)
Abstract Background: Electroencephalography (EEG) recordings under propofol exhibit an increase in slow and alpha oscillations power, and dose-dependent phase-amplitude coupling (PAC), which underlie GABAA potentiation and the central role of thalamocortical entrainment. However, the exact EEG signatures that elicited by volatile anesthetics and the possible neurophysiological mechanisms remain unclear. Methods: Cortical EEG signals and thalamic local field potential (LFP) were recorded in a mice model to detect EEG signatures induced by 0.9%, 1.5% and 2.0% isoflurane. Then the power of the EEG spectrum, thalamocortical coherence and slow-alpha phase amplitude coupling (PAC) were analyzed. A computational model based on thalamic network was used to determine the primary neurophysiological mechanisms of alpha spiking of thalamocortical neurons under isoflurane anesthesia. Results: Isoflurane at 0.9% (light anesthesia) increased the power of slow and delta oscillation both in cortical EEG and thalamic LFP. Isoflurane at 1.5% (surgery anesthesia) increased the power of alpha oscillations both in cortical EEG and thalamic LFP. Isoflurane at 2% (deep anesthesia) further increased the power of cortical alpha oscillations while thalamic alpha oscillations were unchanged. Thalamocortical coherence of alpha oscillation only exhibited a significant increase under 1.5% isoflurane. Isoflurane induced PAC modulation remained unchanged throughout varied concentrations of isoflurane. By adjusting the parameters in the computational model, isoflurane-induced alpha spiking in thalamocortical neurons was simulated, which revealed the potential molecular targets and thalamic network involved in isoflurane-induced alpha spiking in thalamocortical neurons. Conclusions: The EEG changes in the cortical alpha oscillation, thalamocortical coherence and slow-alpha PAC may provide neurophysiological signatures for monitoring isoflurane anesthesia at various depths.